Investigation on FTU dust and on the origin of ferromagnetic and lithiated grains. (30th October 2015) - De Angeli, M.; Laguardia, L.; Maddaluno, G.; Perelli Cippo, E.; Ripamonti, D.; Apicella, M. L.; Bressan, C.; Caniello, R.; Conti, C.; Ghezzi, F.; Grosso, G.; Mazzitelli, G.
Abstract: A comprehensive analysis of composition and morphology of metallic micrometric particles collected in FTU during the 2013 shut-down is presented. The data-set analyzed is the result of years of experimental activity in FTU which is a full metal machine since the beginning of operation and with a liquid lithium limiter (LLL) from 2005. It was found that the metallic population, consisting of flakes, smashed and spheroidally shaped particles from plasma facing components (mainly SS and Mo), exhibits an unexpectedly high, up to 70 wt%, fraction of magnetic grains. The change of crystalline phase from γ to α / δ of the iron component contained in the particles coming from stainless steel is suggested as the mechanism responsible for magnetic dust production. This phase change can be ascribed to the particle temperature quench and/or to the presence of a strong magnetic field during the re-solidification of molten stainless steel droplets. In connection to the dust collected close to the LLL, consisting mainly of lithium carbonate spherical-like particles up to a few mm, the mechanism of Li2 CO3 formation and its role as a source of C and O impurities are discussed.